HPLC based identification of phenolics and biological activities in Elaphomyces mushroom extracts - Funda Ulusu; Bugrahan Emsen; Hacer Sibel Karapinar; Yasin Uzun; Abdullah Kaya (Scientific Reports)
Abstract This study investigated the antioxidant, antibacterial, and cytotoxic properties of extracts from Elaphomyces cyanosporus, E. granulatus, and E. mutabilis mushrooms. The methanol extract of E. mutabilis had the highest total phenol and flavonoid content, with methanol extracts generally showing higher levels than water extracts. HPLC analysis identified gallic acid as the predominant phenolic compound in the E. mutabilis methanol extract (552.3 µg/g), along with chlorogenic acid and quercetin (75.84 µg/g). DPPH radical scavenging activity was highest in the methanol extract of E. granulatus, with the lowest IC50 value in E. mutabilis (38.20 µg/mL), indicating moderate antioxidant capacity. In metal chelation, both E. mutabilis and E. granulatus methanol extracts showed strong activity. Antibacterial tests revealed methanol extracts were more effective than water extracts, with E. cyanosporus showing the highest inhibition against Klebsiella pneumoniae. Cytotoxicity was evaluated on HT-29 human colon cancer and L929 mouse fibroblast cell lines. The methanol extract of E. mutabilis exhibited significant DPPH scavenging, metal chelation, and selective cytotoxicity against HT-29 cells, with minimal effects on normal L929 cells. This selective toxicity suggests potential for developing anticancer agents with limited toxicity to normal cells. These findings highlight the potential for new antibacterial and anticancer agents from mushroom extracts.